2013
DOI: 10.1242/jcs.119214
|View full text |Cite
|
Sign up to set email alerts
|

Novel role of microRNA146b in promoting mammary alveolar progenitor cell maintenance

Abstract: SummaryIn this report, we have shown that miR146b promotes the maintenance of pregnancy-derived mammary luminal alveolar progenitors. MiR146b expression was significantly higher in the mammary glands of pregnant and lactating mice than in virgin mice. Furthermore, miR146b levels were significantly higher in mouse mammary glands exposed to the sex hormones, estrogen and progesterone, compared with those of untreated control animals. Pregnancy-derived primary mouse mammary epithelial cells in which miR146b was k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…It could relate to a general increase in the expression and function of the spliceosome machinery components in these cancer cells [ 49 ] or to alteration in a specific regulatory mechanism(s) normally controlling differential isoform generation. Recently miR146b has been reported to specifically degrade Stat3β in normal mammary luminal cells [ 50 ], suggesting this as a normal mode of regulation. Could the loss of this miRNA in breast cancer cells lead to an aberrant increase in Stat3β in these cells?…”
Section: Discussionmentioning
confidence: 99%
“…It could relate to a general increase in the expression and function of the spliceosome machinery components in these cancer cells [ 49 ] or to alteration in a specific regulatory mechanism(s) normally controlling differential isoform generation. Recently miR146b has been reported to specifically degrade Stat3β in normal mammary luminal cells [ 50 ], suggesting this as a normal mode of regulation. Could the loss of this miRNA in breast cancer cells lead to an aberrant increase in Stat3β in these cells?…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR‐146b is downregulated in monocytes in obese patients, and miR‐146b is a regulator of the anti‐inflammatory, globular adiponectin . miR‐146b also play a role in senescence, mammary alveolar progenitor cell maintenance, erythropoiesis and megakaryocytopoiesis, glioma cell migration and invasion, and myoblast differentiation …”
Section: Introductionmentioning
confidence: 99%
“…12,13 Moreover, miR-146b is downregulated in monocytes in obese patients, and miR-146b is a regulator of the anti-inflammatory, globular adiponectin. 14 miR-146b also play a role in senescence, 15 mammary alveolar progenitor cell maintenance, 16 erythropoiesis and megakaryocytopoiesis, 17 glioma cell migration and invasion, 18 and myoblast differentiation. 19 Figure 1 miR-146b directly downregulates interleukin (IL)-1 receptor-associated kinase (IRAK1) and tumor necrosis factor receptor-associated factor 6 (TRAF6) in macrophages after lipopolysaccharide (LPS) administration in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…The loci encoding miR-193b , miR-146b and miR-148a fulfilled the defining criteria, i.e., binding of STAT5 and PR to putative regulatory sequences, the presence of H3K4me3 and H3K4me2 marks and STAT5-dependent transcription (Figure 1A). While the miR-146a locus is also a bona fide STAT3 target in breast cancer cells (Xiang et al, 2014) and miR-146b controls mammary cell differentiation in vitro (Elsarraj et al, 2013), no pertinent information exists on the roles of the miR-148a and miR-193b loci in mammary development. MiR-193b is unique in that it is expressed significantly only in a few cell types, mammary epithelium, brown adipose tissue (Feuermann et al, 2013; Sun et al, 2011) and hematopoietic progenitor cells (Kuchen et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Studies with primary cells have demonstrated that miR-146b , a known STAT3 target (Xiang et al, 2014), promotes alveolar progenitor cells in a cell line-based organ culture system (Elsarraj et al, 2013). STAT5 and PR are also binding to respective regulatory sequences in this locus further supporting the notion that miR-146b executes hormone function in mammary epithelium.…”
Section: Discussionmentioning
confidence: 99%